Dynamic simulations of many-body electrostatic self-assembly - Lindgren, Eric B.; Stamm, Benjamin; Maday, Yvon; Besley, Elena; Stace, Anthony J. (Royal Society, The, 2018)
Two experimental studies relating to electrostatic self-assembly have been the subject of dynamic computer simulations, where the consequences of changing the charge and the dielectric constant of the materials concerned have been explored. One series of calculations relates to experiments on the assembly of polymer particles that have been subjected to tribocharging and the simulations successfully reproduce many of the observed patterns of behaviour. A second study explores events observed following collisions between single particles and small clusters composed of charged particles derived from a metal oxide composite. As before, observations recorded during the course of the experiments are reproduced by the calculations. One study in particular reveals how particle polarisability can influence the assembly process.